The Impact of HRIS Technologies Adoption on Employee Satisfaction and Retention Rate - Basmantra, Ida Nyoman; Wijaya, David Timothy (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The adoption of Human Resource Information Systems (HRIS) has become increasingly important as organizations pursue digital transformation to enhance both operational performance and employee-related outcomes. This study examines the impact of HRIS adoption on employee satisfaction and employee retention rate, with operational efficiency serving as a mediating variable. The research was conducted in star-rated hotels in Bali, Indonesia, a region characterized by a highly competitive hospitality industry. Using a quantitative approach, data were collected through structured questionnaires distributed to employees who actively use HRIS in their daily work activities. A total of 260 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that HRIS adoption has a strong and positive effect on operational efficiency, indicating that digital HR systems significantly streamline HR processes and reduce administrative complexity. Furthermore, operational efficiency positively influences employee satisfaction and employee retention, confirming its role as a critical organizational mechanism. The results also demonstrate that employee satisfaction acts as a key mediator in the relationship between HRIS adoption and employee retention rate, highlighting satisfaction as the dominant predictor of employees’ intention to remain with the organization. Overall, this study confirms that HRIS should be viewed not merely as an administrative tool but as a strategic human resource system that enhances operational efficiency, improves employee satisfaction, and strengthens employee retention. The findings provide practical insights for organizations seeking to leverage HRIS to achieve sustainable workforce stability.